2021
DOI: 10.1101/2021.12.17.473175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional organization of social perception in the human brain

Abstract: Humans can readily perceive a multitude of features from social interactions, but the phenomenological and neural basis of social perception has yet to be solved. Short film clips with rich social content were shown to 97 healthy participants while their haemodynamic brain activity was measured with fMRI. The stimulus clips were annotated for 112 social features yielding the initial stimulus model. Cluster analysis revealed that 13 dimensions were sufficient for describing the social perceptual space. Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The largest and most generic hub of the neural affective space was the temporo-parietal junction (TPJ), which was activated during the perception and experience of most emotions. TPJ is consistently engaged during social perception 42 and has been previously shown to contain emotion-specific gradients also during perceived and experienced emotions 20 . Accordingly, TPJ activation suggests that social information processing is relevant to most emotions evoked by movies.…”
Section: Discussionmentioning
confidence: 96%
“…The largest and most generic hub of the neural affective space was the temporo-parietal junction (TPJ), which was activated during the perception and experience of most emotions. TPJ is consistently engaged during social perception 42 and has been previously shown to contain emotion-specific gradients also during perceived and experienced emotions 20 . Accordingly, TPJ activation suggests that social information processing is relevant to most emotions evoked by movies.…”
Section: Discussionmentioning
confidence: 96%
“…Recruitment of the pSTS in facial emotion discrimination has been interpreted as the rapid integration of information derived from changeable aspects of the stimuli (e.g., facial expressions, movements) to attribute social and emotional meaning to faces and thereby understand the intentions of others (Walbrin et al, 2018;Zhu et al, 2013). These operations represent an intermediate step between basic perceptual mechanisms and higher-level social processes (Santavirta et al, 2023;Zhu et al, 2013). While the data from Experiment 2 are consistent with previous evidence regarding the pSTS, the critical finding here is that the posterior cerebellum causally contributes to emotion discrimination within the same time window as the pSTS.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that the synchronized STS voxel responses may be explained by similar social feature representations across individuals. The STG and MTG have also been implicated in social cognitive processes, including social signal detection, the integration of verbal and non-verbal social cues, extracting social-affective meaning from observed touch, extracting meaning from speech and perceiving social communication and antisocial behavior ( Price, 2012 ; Sugiura et al ., 2014 ; Holler et al ., 2015 ; Lee Masson et al ., 2018 ; Santavirta et al ., 2023 ). These regions show atypical neural responses to social stimuli in neurodiverse conditions, such as autism and schizophrenia ( Zilbovicius et al ., 2006 ; Redcay, 2008 ; Brent et al ., 2014 ; Köchel et al ., 2015 ; He et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the STS has shown selective neural responses to visually presented social communication ( McMahon et al ., 2023 ) and speech-based social communication ( Landsiedel and Koldewyn, 2023 ). Recent data-driven work has further suggested that communication and antisocial behavior elicit responses in the superior temporal gyrus (STG) and middle temporal gyrus (MTG), respectively ( Santavirta et al ., 2023 ).…”
Section: Introductionmentioning
confidence: 99%